Comparative analysis of unicortical vs. subchondral locking screws in osteoporotic proximal humerus fractures - Mohammad Khak; Jeffrey J. Olson; Patrick Williamson; Mohammad Javad Shariyate; Ahmad Hedayatzadeh Razavi; Kaveh Momenzadeh; Mohammadreza Abbasian; Nadim Kheir; Edward K. Rodriguez; Ara Nazarian (Heliyon)
Background: Proximal humerus fractures are common in adults aged 65 and older and provide challenges for osteoporotic patients due to the risk of suboptimal fixation and complications. Locking plates are often utilized to treat two-part fractures; however, ongoing concerns about their stability exist. This pilot study investigates the biomechanical impact of subchondral locking screws compared to unicortical screws in osteoporotic two-part cadaveric proximal humerus fractures. Methods: Using dual-energy X-ray absorptiometry (DXA), cadaveric shoulder specimens from eight female Caucasian donors with comparable bone mineral densities were used for the study. Either unicortical or bicortical locking screws (the latter representing subchondral screws in real surgeries) were utilized to fix locking plates. Axial load to failure and cyclic physiologic abduction moments were applied in biomechanical testing. Findings: The study found no statistically significant difference in interfragmentary displacement between the unicortical and bicortical groups (p = 0.78). The mechanical properties of both groups were found to be comparable in terms of yield (p = 0.59), ultimate (p = 0.86), and fracture strengths (p = 0.70). Furthermore, rigidity analysis did not identify any significant difference between the two groups (p = 0.22). Interpretation: Our findings indicate that there is little to no difference in the stability of the construct for osteoporotic two-part proximal humerus fractures, in contrast to general recommendations against unicortical screws. This pilot study suggests that the choice between unicortical and subchondral locking screws may not significantly affect biomechanical characteristics in osteoporotic two-part proximal humerus fractures, despite the study's limitations.